The impact of late ADHD diagnosis on mental health outcomes in females - Grace Huynh; Shabana Masood; Hina Mohsin; Adegbemisola Daniyan (Social Sciences and Humanities Open)
Introduction: ADHD presents with long-term symptoms of inattention and hyperactivity-impulsivity that impact one's daily functioning. Compared to girls, boys are twice as likely to be diagnosed with ADHD. Females are more likely to present with symptoms of inattention than hyperactivity, causing their symptoms to be less noticeable in childhood. Due to being diagnosed later, many females experience detrimental impacts from unmanaged ADHD symptoms. Because of the challenges undiagnosed women face, our study hypothesized that later ADHD diagnoses for women contribute to poorer mental health outcomes and an increased risk of developing comorbid conditions. Methods: The National Longitudinal Study of Adolescent and Adult Health (Add Health) Wave IV dataset includes n = 486 males with ADHD and n = 278 females with ADHD, divided into age intervals 1–16 and 17–32. Study participants were stratified by age, gender, and rates of depression and anxiety. Crosstabulation measured the frequency at which each gender was diagnosed at a particular period. Results: There were n = 542 participants in the 1–16 age interval and n = 222 in the 17–32 age interval. The 1–16 interval (younger) had a gender gap of 2.41, with n = 383 males and n = 159 females. The 17–32 interval (older) had a gender gap of 0.87, with n = 103 males and n = 119 females. Females in the younger group had slightly higher rates of mental health comorbidities. In the older group, females had higher rates of anxiety/panic disorder, while males had higher rates of depression. Conclusions: The 17–32 interval had more women than men. Thus, compared to men, women were more likely to receive an ADHD diagnosis at a later age. Rates of comorbid depression and anxiety/panic disorder also varied based on the age of diagnosis and gender. Our study highlights the need to improve the process of diagnosing ADHD in girls.